2018
DOI: 10.1007/s11886-018-1033-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Left Atrial Appendage Amputation During Routine Cardiac Surgery Reduce Future Atrial Fibrillation and Stroke?

Abstract: Purpose of ReviewStroke is the most feared complication of atrial fibrillation. To prevent stroke, left atrial appendage exclusion has been targeted, as it is the prevalent site for formation of heart thrombi during atrial fibrillation.We review the historic development of methods for exclusion of the left atrial appendage and the evidence to support its amputation during routine cardiac surgery.Recent FindingsEvidence is not yet sufficient to routinely recommend left atrial exclusion during heart surgery, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…LAA exclusion or excision may be considered in conjunction with surgical ablation for AF and at the time of cardiac operations in AF patients for thromboembolic prevention (Class IIA, level C expert opinion by the surgical guidelines, whereas the AHA/ACC/HRS guidelines consider it a Class IIB, Level of evidence B‐nonrandomized data) and the European guidelines consider it a Class IIB, Level of Evidence C 61,62,76 . Despite the high prevalence of postoperative AF, there is not sufficient evidence to recommend routine left atrial exclusion during heart surgery 77 …”
Section: Stroke Prevention In Af‐sex Differences In Stroke Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…LAA exclusion or excision may be considered in conjunction with surgical ablation for AF and at the time of cardiac operations in AF patients for thromboembolic prevention (Class IIA, level C expert opinion by the surgical guidelines, whereas the AHA/ACC/HRS guidelines consider it a Class IIB, Level of evidence B‐nonrandomized data) and the European guidelines consider it a Class IIB, Level of Evidence C 61,62,76 . Despite the high prevalence of postoperative AF, there is not sufficient evidence to recommend routine left atrial exclusion during heart surgery 77 …”
Section: Stroke Prevention In Af‐sex Differences In Stroke Riskmentioning
confidence: 99%
“…61,62,76 Despite the high prevalence of postoperative AF, there is not sufficient evidence to recommend routine left atrial exclusion during heart surgery. 77 Surgical occlusion of the LAA (LAAO) includes excision or amputation, and exclusion (clip/stapler, suture ligation). Success rates vary according to surgical procedure with highest success with excision/amputation techniques.…”
Section: Percutaneous Laa Closure Devicesmentioning
confidence: 99%
“…Although the traditional rationale of concomitant surgical LAA amputation was to prevent LAA thrombus formation and subsequent development of stroke, there is mounting interest as to whether or not this may also reduce the burden of AF [45]. However, at present, there is insufficient trial data to support this technique as the main purpose for amputation in routine clinical practice.…”
Section: Surgical Laa Amputationmentioning
confidence: 99%
“… 1 , 2) For many years, intensive research into AF has provided deep insight into the subject while elucidating more knowledge gaps and inadequacies in the current therapeutic options. 3 6) Specifically, the advances in widely adapted catheter ablation technologies have not converted to significant gains in success rates over recent years. 7) It is however important to note that stroke is the most dreaded complication for each AF patient.…”
Section: Introductionmentioning
confidence: 99%
“…The left atrial appendage (LAA) is considered a major source of thromboembolic origin in AF patients. 3) However, some studies have shown that LAA contractile function contributes greatly to left atrial mechanical contraction. 8 10) Moreover, the LAA also plays an important role in body fluid regulation via the secretion of atrial natriuretic peptide (ANP).…”
Section: Introductionmentioning
confidence: 99%